Clinical characteristics, treatment, and survival of thrombocytopenia induced by T-DM1 in early HER2-positive breast cancer - Wang, Fang; Zhang, Xiaosan; Chen, Xiuchun; Zhang, Lu; Liu, Zhenzhen (Frontiers in Oncology, 2025)
BackgroundTrastuzumab emtansine (T-DM1) is widely used for treating both early and advanced HER2-positive breast cancer in China. Thrombocytopenia represents a major adverse event associated with T-DM1 during anti-tumor therapy. Therefore, further exploration is needed to predict and mitigate T-DM1-induced platelet count decrease.Materials and methodsWe conducted a retrospective study utilizing electronic medical records from a single breast cancer center in Henan province. Clinicopathological characteristics and consecutive laboratory examination data were collected for all patients. A total of 63 patients treated with T-DM1 were categorized into two groups: Thrombocytopenia and Non-thrombocytopenia. Statistical analyses employed Chi-squared/Fishers exact test, F-test/Kruskal–Wallis test, logistic regression, and Kaplan–Meier methods.ResultsA total of 63 HER2-positive patients receiving adjuvant T-DM1 were enrolled. A comparison between groups showed that patients in the Thrombocytopenia group were more frequently postmenopausal, had lymph node metastasis, and had undergone radiotherapy. Postmenopausal status was identified as a risk factor for T-DM1-induced thrombocytopenia. Grade ≥2 thrombocytopenia occurred in 30 patients (47.6%) and grade ≥3 thrombocytopenia occurred in 16 patients (25.4%). Patients treated with rhIL-1 1(recombinant human interleukin-11) or rhTPO (recombinant human thrombopoietin) required a longer time for platelet (PLT) recovery to ≥75 × 109/L and ≥100 × 109/L compared to those receiving TPO-Ras (thrombopoietin receptor agonists), although this difference was not statistically significant. The estimated 1-year invasive disease-free survival (IDFS) for all T-DM1-treated patients was 96.8%. The 1-year IDFS rates for the Thrombocytopenia and Non-thrombocytopenia groups were 100.0% and 93.9%, respectively, with no statistically significant difference observed.ConclusionOur findings indicate that T-DM1-induced thrombocytopenia was manageable in this cohort of breast cancer patients. Postmenopausal status correlated with an increased risk of platelet count decrease. Different platelet-producing drugs demonstrated comparable effectiveness in managing thrombocytopenia.